2011
DOI: 10.1371/journal.pone.0026054
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing of Apoptotic DNA Breakpoints Reveals Association with Actively Transcribed Genes and Gene Translocations

Abstract: DNA fragmentation is a well-recognized hallmark of apoptosis. However, the precise DNA sequences cleaved during apoptosis triggered by distinct mechanisms remain unclear. We used next-generation sequencing of DNA fragments generated in Actinomycin D-treated human HL-60 leukemic cells to generate a high-throughput, global map of apoptotic DNA breakpoints. These data highlighted that DNA breaks are non-random and show a significant association with active genes and open chromatin regions. We noted that transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…While the mechanism(s) responsible for the generation of chromothripsis remain elusive, a number of studies have proposed hypotheses including ionizing radiation [9], DNA replication stress [45], breakage-fusion-bridge cycles [9,23,46], premature chromosome compaction [47], failed apoptosis [48,49] and micronuclei formation [50]. Some of these proposed mechanisms are associated with features which could be addressed in our study.…”
Section: Resultsmentioning
confidence: 98%
“…While the mechanism(s) responsible for the generation of chromothripsis remain elusive, a number of studies have proposed hypotheses including ionizing radiation [9], DNA replication stress [45], breakage-fusion-bridge cycles [9,23,46], premature chromosome compaction [47], failed apoptosis [48,49] and micronuclei formation [50]. Some of these proposed mechanisms are associated with features which could be addressed in our study.…”
Section: Resultsmentioning
confidence: 98%
“…Genome sequencing of DNA breaks caused by apoptotic nucleases, like CAD, revealed that they localized at actively transcribed genes, particularly at genes frequently translocated in human cancer. 26 The involvement of sublethal apoptotic signaling in mutagenesis induced by death receptor agonists, mitotic poisons and topoisomerase inhibitors may help define the oncogenic potential of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of a region of the mixed myeloid lineage (MLL) gene could be induced by drugs that target topoisomerases or (to a lesser extent) by apoptotic stimuli including death ligands. 24 , 25 , 26 , 27 The DNA-strand breaks within MLL appeared to involve error-prone repair via non-homologous end joining (NHEJ), which may contribute to the high incidence of chromosomal translocations associated with therapy-related acute myeloid leukemia. 28 CAD has been directly linked to DNA damage in various contexts.…”
mentioning
confidence: 99%
“…Localization of CAD‐induced DNA breaks during these nonapoptotic processes is also of considerable importance. Although apoptotic DNA breaks are largely thought to occur at random across the genome, more recent sequence‐based mapping of the breaks has indicated enrichment at specific sites . Indeed, CAD‐induced DNA breaks that appear during prolonged mitotic arrest localize to telomeric regions.…”
Section: Cad: Perspectivesmentioning
confidence: 99%